The Study of Morbidity Structure in Children Using Automated Computer Technology - Dmitriy Karlov (Journal of Global Pharma Technology, 2020)
The combination of new computer and electronic technologies with methodologies for analysing large databases is considered efficient for increasing the effectiveness of screening methods for detecting diseases. Aim of the research is to study the effectiveness of using an automated complex of dispensary examination (ACDE) for detecting pre-nosology conditions and pathologies of organs and systems in children compering to traditional medical examinations. 948 children aged 6 to 17 years were examined. There were 437 (46.1%) boys and 511 (53.9%) girls. The average age of children was (11.36 ± 1.25) years. First, all children underwent a traditional preventive medical examination, and then a programmed medical examination for all organs and systems using an automated complex of dispensary examinations. The following diseases predominated according to the structure of pathology among the children examined: the musculoskeletal system (in 74.3% of children), cardiac pathology (in 52.5% of children), dental diseases (in 51.4% of children), and diseases of the nervous system (in 48.6% of children) and ophthalmic pathology (in 46.5% of children). The detection frequency of pre-nosology conditions / pathology of organs and systems using the automated complex of dispensary examinations is significantly higher (p